The Result of Counseling Psychology Seminar Model for Enhancing Resilience Quotient of The Fourth Year Majored in Counseling Psychology Intern Students - Somkittikanon, Punvadee; Youngwarasawasd, Rapeepong (Journal of health and health management, 2020)
The purpose of this mixed methods research was to study the result of Counseling Psychology Seminar model for enhancing Resilience Quotient of the fourth year majored in Counseling Psychology intern students. The total of fourth year majored in Counseling Psychology intern students 13 research participants of Seminar in Counseling Psychology subject registration. The research starts from 6th January 2020 to 5 th June 2020. The instruments used in this study consisted of Resilience Quotient Questionnaires of Mental Health Department with the reliability 0.838 and Counseling Psychology Seminar model with Index of item - objective congruence (IOC) ranged from 0.67-1.00. Data were analyzed by descriptive statistics and Wilcoxon Matched Pairs Signed Rank Test. It was found that the overall view and each aspect of the RQ level after the experiment was significantly and higher than before the experiment (p ⁢< .05). Focus group report of the experimental group after the experiment showed that the fourth year intern students can practice at internship place with confidently in communication , counseling service, positive attitude in professional, practical intention and discovery problem solving for clients assistance in several approaches.